Integrated carbon / carbon composite material crucible containing pyrolytic carbon transition coating

By sequentially installing glass-carbon coating, pyrolysis carbon transition coating and yttrium oxide coating on the carbon/carbon composite crucible body, the deformation and cost problems of quartz crucible in traditional single crystal silicon drawing furnaces are solved, and the efficient and economical use of the crucible is achieved.

CN119571441APending Publication Date: 2025-03-07XIAN CHAOMA SCI TECH

Patent Information

Application Number
CN202411569342.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The quartz crucible in traditional single crystal silicon drawing furnaces is prone to deform and soften at high temperatures, resulting in frequent replacement, and the shortage of raw materials for quartz sand and high prices, which increases production costs.

Method used

An integrated carbon/carbon composite crucible containing a pyrolytic carbon transition coating is used. By sequentially installing a glass-carbon coating, a pyrolytic carbon transition coating and a yttrium oxide coating on the inner surface of the carbon/carbon composite crucible body, the thermal stability and silicon corrosion resistance of the crucible are improved.

Benefits of technology

It significantly improves the service life and stability of the crucible, reduces production costs, and ensures high purity of silicon material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571441A_ABST
    Figure CN119571441A_ABST
Patent Text Reader

Abstract

The invention relates to an integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating, and belongs to the technical field of thermal field parts for monocrystalline silicon. The crucible comprises a carbon / carbon composite material crucible body, a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating, wherein the glassy carbon coating not only has a good combination effect with the carbon / carbon composite material crucible body, but also can prevent carbon from escaping; the thermal expansion coefficient of the pyrolytic carbon transition coating is close to that of the glassy carbon coating, and the combination effect of the pyrolytic carbon transition coating and the yttrium oxide coating is good; the yttrium oxide coating has excellent thermal stability and excellent silicon erosion resistance, and can ensure the purity of molten silicon in the single crystal drawing process; the carbon / carbon composite material crucible body is formed by densifying a carbon fiber prefabricated body which is formed by needling and laying a pure net tire sprayed with resin, and the inner surface of the carbon / carbon composite material crucible body is a net tire which is wholly approximately isotropic, so that the overall mechanical strength of the crucible can be ensured, and a good combination effect of the crucible and a subsequent functional coating can also be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating, and belongs to the technical field of thermal field components for single crystal silicon. Background Art

[0002] The single crystal silicon pulling furnace used in traditional single crystal silicon pulling is usually composed of a carbon / carbon crucible and a quartz crucible, that is, the quartz crucible is nested in the carbon / carbon crucible. The quartz crucible plays the role of carrying silicon materials to ensure the purity of silicon materials, while the carbon / carbon crucible plays the role of carrying the quartz crucible and providing strength support. The temperature inside the single crystal silicon pulling furnace is as high as 1500℃. The quartz crucible holding the silicon materials will have problems such as deformation and softening, and replacement is very frequent. About 1 carbon / carbon crucible will consume 12 to 18 quartz crucibles. In addition, the raw material quartz sand for the production of quartz crucibles is relatively scarce. In recent years, the rapid increase in the price of high-purity quartz sand and the imbalance between supply and demand have led to high crystal pulling costs.

[0003] Carbon / carbon composite materials are composite materials formed by carbon fiber or various carbon fabrics reinforced with carbon matrix. They have excellent properties such as low density, high specific strength, wear resistance, and high temperature resistance. They are currently widely used in aerospace, metallurgy, new energy and other fields. At present, researchers have proposed the use of "integrated carbon / carbon composite crucibles" to replace the traditional "combination of carbon / carbon crucibles and quartz crucibles". On the one hand, it can avoid the impact of the rapid rise in the price of high-purity quartz sand and reduce the material cost of crystal pulling. On the other hand, the integrated design can combine materials and performance into one, maximize its advantages, and further reduce product costs.

[0004] The integrated carbon / carbon composite crucible is formed by densifying the carbon fiber preform to form a carbon / carbon composite crucible body, and then preparing a high-performance coating on the inner surface of the carbon / carbon composite crucible body. For example, patent CN103102170A prepares SiC coating and Si3N4 coating on the inner surface of the carbon / carbon composite crucible body, which can significantly increase the number of times the crucible can be used and significantly improve its life. However, the surface of the Si3N4 coating is relatively rough and has a certain wettability to silicon. There is a risk of damaging the Si3N4 coating during the production process of single crystal silicon.

[0005] In addition, the carbon fiber preform is the blank for preparing carbon / carbon composite crucibles, which directly affects the service life of crucible products. The disclosed carbon fiber preform is usually prepared by laminating a layer unit consisting of a carbon fiber woven cloth / carbon fiber mesh layer combined with a carbon fiber filament winding layer. Although the carbon fiber preform has high mechanical strength and good shaping effect, due to the presence of the carbon fiber woven cloth on its inner surface, the surface roughness is low and the bonding with the subsequent functional coating is poor, which will greatly affect the service life of the crucible product. Summary of the invention

[0006] In view of this, the present invention provides an integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating, wherein a glass carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating are sequentially arranged on the inner surface of the carbon / carbon composite material crucible body, the glass carbon coating has a high thermal matching degree with the crucible body, a good bonding effect, and can effectively prevent the escape of carbon in the crucible body; the surface of the pyrolytic carbon transition coating is a rough structure, and has a similar thermal expansion coefficient to the glass carbon coating. Compared with the dense and smooth surface of the glass carbon coating, the yttrium oxide coating prepared on the pyrolytic carbon transition coating can effectively improve the bonding effect of the coating; the yttrium oxide coating has excellent thermal stability, excellent resistance to silicon corrosion, and can ensure the purity of molten silicon in the process of pulling single crystals. In addition, the carbon / carbon composite material crucible body is formed by a carbon fiber preform made of a pure mesh tire needle-punched layer of sprayed resin, and its inner surface is a mesh tire that is nearly isotropic as a whole, which can not only ensure the overall mechanical strength of the crucible, but also ensure a good bonding effect with the subsequent functional coating, thereby increasing the service life of the crucible.

[0007] The objectives of the present invention are achieved through the following technical solutions.

[0008] An integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating, the crucible comprising a carbon / carbon composite material crucible body, a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating, the glassy carbon coating being in contact with the inner surface of the carbon / carbon composite material crucible body, and the pyrolytic carbon transition coating being located between the glassy carbon coating and the yttrium oxide coating;

[0009] The carbon / carbon composite crucible body is prepared by carbon densification of a carbon fiber preform; the carbon fiber preform is a structure composed of alternately stacked carbon fiber mesh needle-punched layers and resin layers sprayed on the outer surface of the carbon fiber mesh needle-punched layers.

[0010] Furthermore, the thickness of the glassy carbon coating is 50 to 300 μm.

[0011] Furthermore, the thickness of the pyrolytic carbon transition coating is 10 to 100 μm.

[0012] Furthermore, the thickness of the yttrium oxide coating is 100-500 μm.

[0013] Furthermore, the density of the carbon fiber preform is 0.30-0.50 g / cm 3 The density of the carbon / carbon composite crucible body is 1.50-1.70 g / cm 3 .

[0014] Furthermore, the glassy carbon coating is prepared by a resin impregnation carbonization process, which specifically includes the following preparation steps:

[0015] The carbon / carbon composite material crucible body is first impregnated in resin, impregnated for 0.5 to 5 hours at an impregnation pressure of 1 to 3 MPa, then heated to 100 to 300° C. at a heating rate of 1 to 3° C. / h and cured at 100 to 300° C. for 3 to 5 hours, then heated to 900 to 1100° C. at a heating rate of 1 to 5° C. / h and carbonized at 900 to 1100° C. for 5 to 10 hours, thereby forming the glassy carbon coating on the inner surface of the carbon / carbon composite material crucible body;

[0016] The resin is preferably furfural resin or phenolic resin.

[0017] Furthermore, the pyrolytic carbon transition coating is prepared by a chemical vapor deposition process, which specifically includes the following preparation steps:

[0018] Propylene or natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 10-50 L / min, the deposition temperature is 900-1100° C., and the total deposition time is 10-30 h.

[0019] Furthermore, the yttrium oxide coating is prepared by a plasma spraying process, and the process parameters of the plasma spraying include: the particle size of the yttrium oxide powder is 10 to 100 μm, the carrier gas (such as nitrogen) pressure is 0.2 to 3 MPa, the auxiliary gas (such as hydrogen) pressure is 0.1 to 2 MPa, the current is 300 to 900 A, the voltage is 40 to 120 V, and the spraying distance is 30 to 180 mm.

[0020] Furthermore, the carbon fiber preform is subjected to pyrolytic carbonization and resin carbonization densification treatment in sequence by using a chemical vapor infiltration process combined with a resin impregnation carbonization process, that is, the carbon fiber preform is first subjected to pyrolytic carbonization densification treatment by using a chemical vapor infiltration process and the density is increased to 1.0-1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.50-1.70 g / cm 3 , then a carbon / carbon composite material crucible body is obtained;

[0021] Preferably, the parameters of the chemical vapor infiltration process are as follows: propylene or natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 10-50 L / min, the deposition temperature is 900-1100°C, and the total deposition time is 80-120 h; the parameters of the resin impregnation carbonization process are as follows: furfural resin or phenolic resin is used as the impregnating agent, impregnated for 0.5-5 h at an impregnation pressure of 1.0-3.0 MPa, then cured at a curing temperature of 100-300°C for 1-10 h, and then carbonized at a carbonization temperature of 900-1000°C for 2-6 h, and the heating rate of the curing and carbonization process is 10-20°C / h.

[0022] Furthermore, the carbon fiber preform comprises the following specific preparation steps:

[0023] (1) A carbon fiber web is needle-punched and laid on a core mold to form a web layer;

[0024] (2) spraying a layer of resin on the surface of the web layer to form a resin layer;

[0025] (3) Repeating the operations of steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer and a resin layer on the surface of the resin layer in step (2), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0026] (4) Curing the preform precursor obtained in step (3) to obtain the carbon fiber preform.

[0027] Furthermore, step (1) uses a soft core mold, which is convenient for needle punching, such as a wooden core mold or a rubber core mold; and before the curing treatment in step (4), the soft core mold is preferably replaced with a hard core mold, such as a metal core mold or a graphite core mold, to avoid deformation of the core mold during the curing treatment.

[0028] Furthermore, the carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 .

[0029] Furthermore, the needle punching density of the web layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.

[0030] Furthermore, the resin used for spraying the resin layer is furfural resin or phenolic resin.

[0031] Furthermore, the resin spraying amount of the resin layer is 0.5 to 1.5 L / cm 2 .

[0032] Furthermore, the curing conditions are as follows: curing pressure is 1.0-3.0 MPa, curing temperature is 100-250° C., and curing time is 3-5 h.

[0033] Furthermore, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction it is divided into a crucible straight section, a crucible R-angle transition section, and a crucible bottom surface. Then, the thickness of the crucible straight section in the carbon fiber preform is less than the thickness of the crucible R-angle transition section, and the thickness of the crucible R-angle transition section is less than or equal to the thickness of the crucible bottom surface.

[0034] Furthermore, the thicknesses of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible in the carbon fiber preform are 200-500 mm, 300-600 mm, and 400-800 mm, respectively.

[0035] Furthermore, a layer of web layer and a layer of resin layer form a layer unit, and the thickness of a layer unit is 5-10 mm. The difference in thickness of the crucible straight tube section, the crucible R angle transition section and the bottom surface of the crucible in the preform lies in the different number of layer units.

[0036] Beneficial effects:

[0037] (1) The present application sequentially prepares a glassy carbon coating, a pyrolytic carbon transition coating, and an yttrium oxide coating on the crucible body as a composite functional coating. The porosity of the glassy carbon coating is approximately zero, and the surface is more dense, which can effectively prevent the carbon from escaping from the crucible body. Moreover, the glassy carbon and the carbon in the crucible body are of the same substance, with a high thermal match and good bonding effect with the crucible body. However, the glassy carbon coating has a dense and smooth structure, and the bonding performance of the yttrium oxide coating with it is relatively weak, so the yttrium oxide coating is prone to falling off. The pyrolytic carbon coating is introduced between the glassy carbon coating and the yttrium oxide coating. On the one hand, the dense pyrolytic carbon coating can further prevent the escape of carbon from the crucible body. At the same time, the pyrolytic carbon and the glassy carbon are both carbonaceous materials with similar thermal expansion coefficients. Therefore, the two have excellent bonding performance. On the other hand, the surface state of the pyrolytic carbon coating is a rough structure, and the yttrium oxide coating can be embedded in the surface of the pyrolytic carbon coating. The two have strong bonding performance, thereby improving the problem of the yttrium oxide coating falling off easily. Yttrium oxide coating does not introduce impurities during the molten silicon process, meeting the requirements of crystal pulling. Moreover, the valence bond structure of yttrium oxide itself makes it difficult for silicon to enter the interior of yttrium oxide at high temperatures, and it has excellent resistance to silicon corrosion. In addition, compared with aluminum oxide coating, yttrium oxide coating has higher temperature resistance, and no phase change occurs at high temperatures, further increasing the stability of yttrium oxide coating.

[0038] (2) The present invention uses a carbon fiber mesh with sprayed resin to prepare the carbon fiber preform of the crucible. On the one hand, the sprayed resin can play a mechanical supporting role between the mesh layers after curing treatment, ensuring the overall mechanical properties of the crucible product, and can also make the carbon fiber preform structure hardened and not easy to deform, which is more conducive to transportation and storage; on the other hand, the nearly isotropic pure mesh layer is used as the inner surface of the carbon fiber preform, which has a certain roughness and uniform surface quality, which is not only conducive to the preparation of subsequent functional coatings, but also improves the bonding performance of the functional coating with the crucible substrate, solving the problem of affecting the service life of the crucible product due to the easy shedding of the functional coating. In addition, compared with the carbon fiber preform made of carbon fiber woven cloth, carbon fiber mesh and carbon fiber filament, the process operation of the carbon fiber preform made of pure mesh in the present invention is simpler and the preparation cycle is short.

[0039] (3) The resin impregnation carbonization process used in this application can meet the requirements of large-scale, batch-scale glassy carbon coating preparation. It should be noted that in the preparation of glassy carbon coating, the heating rate of the curing and carbonization process is an important factor affecting the density of the coating. If the heating rate is too fast, the glassy carbon coating will have defects such as microcracks and pores. If the heating rate is too slow, the production cost will be greatly increased.

[0040] (4) The present application utilizes plasma spraying technology to prepare yttrium oxide coatings, which have controllable thickness, low porosity, high quality consistency, high preparation efficiency, and are suitable for mass production.

[0041] (5) Based on the structural characteristics of the crucible itself, it can be seen that the stress concentration is the greatest at the R corner, which is prone to fatigue cracks. Increasing the thickness here can effectively make the straight tube section transition smoothly to the bottom surface, reducing the stress concentration problem at the R corner; in addition, affected by the actual working conditions, the R corner and the bottom surface are most affected by the gravity of the silicon melt. Increasing the thickness of these two places can effectively prevent the occurrence of "silicon leakage"; and setting different thicknesses for different areas can effectively reduce the overall weight of the carbon fiber preform and reduce the manufacturing cost of the crucible product on the basis of ensuring the overall mechanical properties of the crucible product. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of the structure of the integrated carbon / carbon composite crucible containing a pyrolytic carbon transition coating prepared in Example 1.

[0043] Among them, 1-carbon / carbon composite material crucible body, 2-glass carbon coating, 3-pyrolytic carbon transition coating, 4-yttrium oxide coating. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified. In addition, in the description of the present invention, it should be understood that the orientations or positional relationships indicated by the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation to the present invention.

[0045] Example 1

[0046] The integrated carbon / carbon composite material crucible containing the pyrolytic carbon transition coating 3 specifically comprises the following preparation steps:

[0047] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0048] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 50g / m 2 The felt has a needle density of 10 needles / cm 2 , the needling depth is 5 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0049] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 0.5L / cm 2 , forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 5 mm;

[0050] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer units formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0051] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 200 mm, 300 mm, and 400 mm, respectively.

[0052] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 1.0 MPa and a temperature of 250° C. for curing for 3 h to obtain a density of 0.30 g / cm 3 Carbon fiber preform;

[0053] (5) First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.0 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.50g / cm 3 , then a carbon / carbon composite material crucible body 1 is obtained;

[0054] The parameters of the chemical vapor infiltration process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 10 L / min, the deposition temperature is 900°C, and the total deposition time is 80 h;

[0055] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnating agent, impregnated at an impregnation pressure of 1.0 MPa for 0.5 h, then cured at a curing temperature of 100 °C for 1 h, and then carbonized at a carbonization temperature of 900 °C for 2 h, and the heating rate of the curing and carbonization process is 10 °C / h;

[0056] (6) The carbon / carbon composite crucible body 1 is first immersed in furfural resin, immersed for 0.5 h at an immersion pressure of 1.0 MPa, then heated to 100°C at a heating rate of 1°C / h and cured at 100°C for 3 h, and then heated to 900°C at a heating rate of 1°C / h and carbonized at 900°C for 5 h, thereby forming a glassy carbon coating 2 with a thickness of 50 μm on the inner surface of the carbon / carbon composite crucible body 1;

[0057] (7) preparing a pyrolytic carbon transition coating 3 with a thickness of 10 μm on the glassy carbon coating 2 by a chemical vapor deposition process;

[0058] The parameters of the chemical vapor deposition process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 10 L / min, the deposition temperature is 900 °C, and the total deposition time is 10 h;

[0059] (8) A yttrium oxide coating 4 with a thickness of 500 μm is prepared on the pyrolytic carbon transition coating 3 by a plasma spraying process, and the preparation of the crucible is completed accordingly, such as Figure 1 As shown;

[0060] The process parameters of plasma spraying include: the particle size of yttrium oxide powder is 100 μm, the pressure of carrier gas (such as nitrogen) is 3.0 MPa, the pressure of auxiliary gas (such as hydrogen) is 2.0 MPa, the current is 900 A, the voltage is 120 V, and the spraying distance is 30 mm.

[0061] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 200 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 8.78×10 16 atoms / cm 3 , oxygen content is 1.52×10 17 atoms / cm 3 .

[0062] Example 2

[0063] The integrated carbon / carbon composite material crucible containing the pyrolytic carbon transition coating 3 specifically comprises the following preparation steps:

[0064] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0065] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 300g / m 2 The felt has a needle density of 30 needles / cm 2 , the needling depth is 8 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0066] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 1.0 L / cm 2 , forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 8 mm;

[0067] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0068] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 350 mm, 500 mm, and 600 mm, respectively.

[0069] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 2.0 MPa and a temperature of 180° C. for curing for 4 h to obtain a density of 0.40 g / cm 3 Carbon fiber preform;

[0070] (5) First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.10 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.60g / cm 3 , then a carbon / carbon composite material crucible body 1 is obtained;

[0071] The parameters of the chemical vapor infiltration process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 30 L / min, the deposition temperature is 1000 °C, and the total deposition time is 100 h;

[0072] The parameters of the resin impregnation carbonization process are as follows: phenolic resin is used as the impregnating agent, impregnated for 3 h at an impregnation pressure of 2.0 MPa, then cured at a curing temperature of 200 °C for 6 h, and then carbonized at a carbonization temperature of 950 °C for 4 h. The heating rate of the curing and carbonization process is 15 °C / h;

[0073] (6) The carbon / carbon composite crucible body 1 is first immersed in phenolic resin at an immersion pressure of 2.0 MPa for 1.5 h, then heated to 200° C. at a heating rate of 2° C. / h and cured at 200° C. for 4 h, then heated to 1000° C. at a heating rate of 3° C. / h and carbonized at 1000° C. for 7 h, thereby forming a glassy carbon coating 2 with a thickness of 180 μm on the inner surface of the carbon / carbon composite crucible body 1;

[0074] (7) preparing a pyrolytic carbon transition coating 3 with a thickness of 60 μm on the glassy carbon coating 2 by a chemical vapor deposition process;

[0075] The parameters of the chemical vapor deposition process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 30 L / min, the deposition temperature is 1000 °C, and the total deposition time is 20 h;

[0076] (8) preparing a yttrium oxide coating 4 with a thickness of 300 μm on the pyrolytic carbon transition coating 3 by a plasma spraying process, and completing the preparation of the crucible accordingly;

[0077] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 55μm, the carrier gas (such as nitrogen) pressure is 1.8MPa, the auxiliary gas (such as hydrogen) pressure is 1.0MPa, the current is 600A, the voltage is 80V, and the spraying distance is 100mm.

[0078] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 160 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 13.50×10 16 atoms / cm 3 , oxygen content is 2.08×10 17 atoms / cm 3 .

[0079] Example 3

[0080] The integrated carbon / carbon composite material crucible containing the pyrolytic carbon transition coating 3 specifically comprises the following preparation steps:

[0081] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0082] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 500g / m 2 The felt has a needle density of 50 needles / cm 2 , the needling depth is 10 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0083] (2) Spray a layer of phenolic resin on the surface of the mesh layer at a spray volume of 1.5L / cm 2 , forming a resin layer; at this time, the web layer after spraying the phenolic resin is a ply unit (including the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 10 mm;

[0084] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0085] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 500 mm, 600 mm, and 800 mm, respectively.

[0086] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 3.0 MPa and a temperature of 100° C. for curing for 5 h to obtain a density of 0.50 g / cm 3 Carbon fiber preform;

[0087] (5) First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.70g / cm 3 , then a carbon / carbon composite material crucible body 1 is obtained;

[0088] The parameters of the chemical vapor infiltration process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 50 L / min, the deposition temperature is 1100°C, and the total deposition time is 120 h;

[0089] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnating agent, impregnated at an impregnation pressure of 3.0 MPa for 5 h, then cured at a curing temperature of 300 °C for 10 h, and then carbonized at a carbonization temperature of 1000 °C for 6 h. The heating rate of the curing and carbonization process is 20 °C / h;

[0090] (6) The carbon / carbon composite crucible body 1 is first immersed in phenolic resin at an immersion pressure of 3.0 MPa for 2 h, then heated to 300° C. at a heating rate of 3° C. / h and cured at 300° C. for 5 h, then heated to 1100° C. at a heating rate of 5° C. / h and carbonized at 1100° C. for 10 h, thereby forming a glassy carbon coating 2 with a thickness of 300 μm on the inner surface of the carbon / carbon composite crucible body 1;

[0091] (7) preparing a pyrolytic carbon transition coating 3 with a thickness of 100 μm on the glassy carbon coating 2 by a chemical vapor deposition process;

[0092] The parameters of the chemical vapor deposition process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 50 L / min, the deposition temperature is 1100 °C, and the total deposition time is 30 h;

[0093] (8) preparing a yttrium oxide coating 4 with a thickness of 100 μm on the pyrolytic carbon transition coating 3 by a plasma spraying process;

[0094] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 10μm, the carrier gas (such as nitrogen) pressure is 0.2MPa, the auxiliary gas (such as hydrogen) pressure is 0.1MPa, the current is 300A, the voltage is 40V, and the spraying distance is 180mm.

[0095] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 130 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 25.40×10 16 atoms / cm 3 , oxygen content is 3.34×10 17 atoms / cm 3 .

[0096] Comparative Example 1

[0097] On the basis of Example 1, only the process of preparing the pyrolytic carbon transition coating 3 on the glassy carbon coating 2 in step (7) is omitted. That is, the yttrium oxide coating 4 is directly prepared on the glassy carbon coating 2 according to the process conditions of step (8). The other steps and preparation conditions are the same as those in Example 1, and an integrated carbon / carbon composite material crucible without the pyrolytic carbon transition coating 3 is obtained accordingly.

[0098] The crucible prepared in Comparative Example 1 was used to pull silicon rods in a single crystal furnace, and the crucible coating was kept stable for 170 hours (crystal pulling was continued in the crucible. When the liquid level was stable and no bubbles overflowed, it indicated that the coating was stable; when bubbles escaped, it indicated that the coating failed). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting were tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content was 13.70×10 16 atoms / cm 3 , oxygen content is 1.67×10 17 atoms / cm 3 .

[0099] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An integrated carbon / carbon composite crucible with a pyrolytic carbon transition coating, characterized in that: The crucible comprises a carbon / carbon composite crucible body, a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating, wherein the glassy carbon coating contacts the inner surface of the carbon / carbon composite crucible body, and the pyrolytic carbon transition coating is located between the glassy carbon coating and the yttrium oxide coating; The carbon / carbon composite crucible body is prepared by carbon densification of a carbon fiber preform; the carbon fiber preform is a structure composed of alternately stacked carbon fiber mesh needle-punched layers and resin layers sprayed on the outer surface of the carbon fiber mesh needle-punched layers.

2. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 1, characterized in that: The thickness of the glassy carbon coating is 50 to 300 μm; Or / and, the thickness of the pyrolytic carbon transition coating is 10 to 100 μm; Or / and, the thickness of the yttrium oxide coating is 100-500 μm.

3. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 1 or 2, characterized in that: The density of the carbon fiber preform is 0.30 to 0.50 g / cm 3 The density of the carbon / carbon composite crucible body is 1.50-1.70 g / cm 3 .

4. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 1 or 2, characterized in that: The glassy carbon coating is prepared by a resin impregnation carbonization process, which specifically includes the following preparation steps: firstly immersing a carbon / carbon composite material crucible body in a resin, immersing for 0.5 to 5 hours at an impregnation pressure of 1 to 3 MPa, then heating to 100 to 300° C. at a heating rate of 1 to 3° C. / h and curing at 100 to 300° C. for 3 to 5 hours, then heating to 900 to 1100° C. at a heating rate of 1 to 5° C. / h and carbonizing at 900 to 1100° C. for 5 to 10 hours, thereby forming the glassy carbon coating on the inner surface of the carbon / carbon composite material crucible body; Or / and, the pyrolytic carbon transition coating is prepared by chemical vapor deposition process, which specifically includes the following preparation steps: using propylene or natural gas as carbon source gas, the flow rate of carbon source gas is 10-50L / min, the deposition temperature is 900-1100°C, and the total deposition time is 10-30h; Or / and, the yttrium oxide coating is prepared by a plasma spraying process, the process parameters of the plasma spraying include: the particle size of the yttrium oxide powder is 10 to 100 μm, the carrier gas pressure is 0.2 to 3 MPa, the auxiliary gas pressure is 0.1 to 2 MPa, the current is 300 to 900 A, the voltage is 40 to 120 V, and the spraying distance is 30 to 180 mm.

5. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 3, characterized in that: First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment by chemical vapor infiltration process and the density is increased to 1.0-1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.50-1.70 g / cm 3 , then a carbon / carbon composite material crucible body is obtained.

6. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 1, characterized in that: The carbon fiber preform comprises the following specific preparation steps: (1) A carbon fiber web is needle-punched and laid on a core mold to form a web layer; (2) spraying a layer of resin on the surface of the web layer to form a resin layer; (3) Repeating the operations of steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer and a resin layer on the surface of the resin layer in step (2), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor; (4) Curing the preform precursor obtained in step (3) to obtain the carbon fiber preform.

7. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 6, characterized in that: The carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 ; Or / and, the needle punching density of the web layer is 10 to 50 needles / cm 2 , acupuncture depth 5 to 10 mm; Or / and, the resin used for spraying the resin layer is furfural resin or phenolic resin; Or / and, the resin spraying amount of the resin layer is 0.5-1.5L / cm 2 .

8. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 6 or 7, characterized in that: The curing conditions are as follows: curing pressure is 1.0-3.0 MPa, curing temperature is 100-250° C., and curing time is 3-5 h.

9. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 6 or 7, characterized in that: According to the structure of the integrated crucible, the crucible is divided into a straight section of the crucible, a R-angle transition section of the crucible, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. The thickness of the straight section of the crucible in the carbon fiber preform is less than the thickness of the R-angle transition section of the crucible, the thickness of the R-angle transition section of the crucible is less than or equal to the thickness of the bottom surface of the crucible, and the thicknesses of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible are 200-500 mm, 300-600 mm, and 400-800 mm, respectively.

10. The integrated carbon / carbon composite material crucible containing a pyrolytic carbon transition coating according to claim 9, characterized in that: A layer of web layer and a layer of resin layer constitute a ply unit, and the thickness of a ply unit is 5 to 10 mm; The difference in thickness between the straight section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible lies in the different numbers of the layering units.

Citation Information

Patent Citations

  • Crucible and preparation method thereof

    CN103102170A

Cited By

  • Preparation method of high-oxidation-resistance pyrolytic carbon coating of carbon fiber thermal insulation material

    CN120483772A